Effects of low temperature annealing on the photo-electrochemical performance of tin-doped hematite photo-anodes. (10th October 2017) - Bedoya-Lora, Franky E.; Hankin, Anna; Holmes-Gentle, Isaac; Regoutz, Anna; Nania, Manuela; Payne, David J.; Cabral, João T.; Kelsall, Geoff H.
Abstract: The effects of post-deposition annealing at 400 and 500 °C on the photo-electrochemical performance of Sn IV -doped α-Fe2 O3 photo-anodes are reported. Samples were fabricated by spray pyrolysis on fluorine-doped tin oxide (FTO) and on titanium substrates. Photo-electrochemical, morphological and optical properties were determined to explain the shift in photocurrent densities to lower electrode potentials and the decrease of maximum photocurrent densities for alkaline water oxidation after annealing. Annealing at 400 and 500 °C in air did not affect significantly the morphology, crystallinity, optical absorption or spatial distributions of oxygen vacancy concentrations. However, XPS data showed a redistribution of Sn IV near Sn IV -doped α-Fe2 O3 | 1 M NaOH interfaces after annealing. Thus, electron-hole recombination rates at photo-anode surfaces decreased after annealing, shifting photocurrents to lower electrode potentials. Conversely, depletion of Sn IV in the α-Fe2 O3 bulk could increase recombination rates therein and decrease photon absorption near 550 nm, due to an increased dopant concentration in the semiconductor depletion layer. This accounted for the decrease of maximum photocurrents when electron-hole recombination rates were suppressed using HO2 − ions as a hole scavenger. The flat band potential of Sn IV -doped α-Fe2 O3 remained relatively constant at ca. 0.7 V vs. RHE, irrespective of annealing conditions.